Pelaksanaan Festival Anak Soleh Untuk Menggali Potensi Dan Meningkatkan Talenta Anak Dalam Rangka Peringatan 1 Muharram 1445 H Di Bah Jambi, Simalungun - Dina Aulia Yudistira Munthe; Fadiah Adlina; Linda Damayanti; Lutfi Aulia; Pipi Andriani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Commemoration of 1 Muharram 1445 H as the beginning of the Hijriyah year which has sacred value in the lives of Muslims. So a pious children's festival was held to celebrate it. The implementation of the Soleh Children's Festival is not just about celebration, but rather a meaningful journey to create an environment that stimulates and empowers children, so that they can grow into individuals with potential and unlimited talents. This research uses a qualitative descriptive method. The results of this research are that there are several children's competencies that can be improved in this pious children's festival event, namely: (1) encouraging children to hone their abilities to learn more about themselves and master their potential and talents in participating in activities, (2) it is beneficial for children to get children used to appearing in public with confidence and developing their potential and talents.